CONSUMER PROTECTION IN THE PURCHASE OF RECONDITIONED ELECTRONIC GOODS IN BANDA ACEH: An analysis of Islamic law and Law No. 8 of 1999 on Consumer Protection - M. Farhan (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This study aims to analyse legal protection for consumers in the purchase of reconditioned electronic goods in Banda Aceh, viewed from the perspective of Islamic law and Law No. 8 of 1999 on Consumer Protection. The research method employed is a qualitative approach, utilising data collection techniques that include literature reviews, field observations, and interviews with consumers and business actors. The results of the study indicate that many business operators use ambiguous terms, such as "used goods" or "ex-inter," without providing transparent explanations, which can obscure the status of the goods as refurbished. Although some consumers are aware of the meaning of these terms, they do not fully understand the risks and quality of the goods they purchase. From an Islamic law perspective, such practices may fall under the categories of tadlis and gharar, which are prohibited in sales contracts. Meanwhile, according to Law No. 8 of 1999, this practice contradicts the obligation of business operators to provide honest information and consumers' right to clarity regarding the goods they purchase. Challenges in implementing consumer protection include low consumer legal literacy, weak oversight of reconditioned product sales, and limited effectiveness of dispute resolution mechanisms. This study recommends strengthening regulations, consumer education, and enforcing principles of transparency and Islamic business ethics as efforts to achieve more optimal protection.